Factors Predicting Treatment Adherence Among Patients with Hypertension: A Systematic Review and Meta-Analysis - Thandar Win; Sureeporn Thanaslip; Rapin Polsook (National Journal of Community Medicine, 2025)
Background: Through the increased prevalence of hypertension, the notch of following the prescribed anti-hypertensive treatment among these populations is very inadequate, and the unsatisfactory disease control rate. This study systematically reviewed and identified their characteristics of the predicting factors on it and their magnitude.